2014
DOI: 10.4172/2375-4427.1000117
|View full text |Cite
|
Sign up to set email alerts
|

The Phonics Approach in Swedish Children using Cochlear Implants or Hearing Aids: Inspecting Phonological Gain

Abstract: The present study investigated cognitive abilities (i.e. Phonological Processing Skills (PhPS), lexical access, complex and visual Working Memory (WM), and letter knowledge) in Deaf and Hard of Hearing children (DHH) 5, 6 and 7 years of age using cochlear implants or hearing aids. Children with Normal Hearing (NH) served as a reference group. All children took part of a computer-assisted intervention with a phonics approach for 4 weeks aimed to support PhPS. The first aim of the study was to examine associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In these studies, children on average practiced with the program for 7 min each day for 4 weeks. The results were promising, particularly for DHH children with an initially weak phonological status, who improved their phonological skills (Nakeva von Mentzer, 2014b). Also, a significant correlation between letter knowledge and phonological gain was observed only in children with weak phonological skills.…”
Section: Computer-based Phonicsmentioning
confidence: 85%
See 2 more Smart Citations
“…In these studies, children on average practiced with the program for 7 min each day for 4 weeks. The results were promising, particularly for DHH children with an initially weak phonological status, who improved their phonological skills (Nakeva von Mentzer, 2014b). Also, a significant correlation between letter knowledge and phonological gain was observed only in children with weak phonological skills.…”
Section: Computer-based Phonicsmentioning
confidence: 85%
“…Several studies have reported a positive effect of GG on word-decoding ability in elementary school children at risk for reading disorders (Kyle et al, 2013;Lyytinen et al, 2009;Saine et al, 2011). During 2010-2012, a Swedish version of GG served as an intervention tool for deaf and hard of hearing (DHH) children using cochlear implants and/or hearing aids (Nakeva von Mentzer et al, 2013, 2014a, 2014b. In these studies, children on average practiced with the program for 7 min each day for 4 weeks.…”
Section: Computer-based Phonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…With a small vocabulary, an underdeveloped semantic structure (i.e., the taxonomic, associative or similarity-based relations between words) could also be expected, but research indicates a large heterogeneity among DHH children (Peterson et al, 2010 ; Löfkvist et al, 2012 ; Kenett et al, 2013 ; Li et al, 2013 ; Nakeva von Mentzer, 2014 ). In fact, semantic and other cognitive cues may play a more important role in linguistic processing of DHH children, as a means to compensate for poor phonological skills (Lyxell et al, 2009 ; Nakeva von Mentzer et al, 2014a ). What cannot be extracted from the speech signal bottom-up might be inferred using top-down processes (Wingfield and Tun, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sound awareness helps children to classify words coming from the speech and then write them. Nakeva et al [22] argued that children with difficulties with the phonological representation task were older when diagnosed and had an older age at amplification. Further, these children displayed broader cognitive difficulties, suggesting that reduced access to auditory stimulation may have wide-ranging effects on cognitive development.…”
Section: Discussionmentioning
confidence: 99%